2015
DOI: 10.1128/aac.01304-15
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of AAC(6′)-Ib-Mediated Resistance to Amikacin in Acinetobacter baumannii by an Antisense Peptide-Conjugated 2′,4′-Bridged Nucleic Acid-NC-DNA Hybrid Oligomer

Abstract: bMultiresistant Acinetobacter baumannii, a common etiologic agent of severe nosocomial infections in compromised hosts, usually harbors aac(6=)-Ib. This gene specifies resistance to amikacin and other aminoglycosides, seriously limiting the effectiveness of these antibiotics. An antisense oligodeoxynucleotide (ODN4) that binds to a duplicated sequence on the aac(6=)-Ib mRNA, one of the copies overlapping the initiation codon, efficiently inhibited translation in vitro. An isosequential nuclease-resistant hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 54 publications
(81 reference statements)
0
41
0
Order By: Relevance
“…1B), is now available, we also generated chimeric oligomers containing these analogs and tested their efficiency as EGSs. We recently showed that antisense oligonucleotide analogs composed of BNA NC and DNA residues efficiently interfered with gene expression by steric hindrance when used as antisense compounds targeting the translation initiation region of aac(6ʹ)-Ib [37]. Therefore, we decided to compare the activity of LNA/DNA with that of BNA NC /DNA oligomers as EGSs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1B), is now available, we also generated chimeric oligomers containing these analogs and tested their efficiency as EGSs. We recently showed that antisense oligonucleotide analogs composed of BNA NC and DNA residues efficiently interfered with gene expression by steric hindrance when used as antisense compounds targeting the translation initiation region of aac(6ʹ)-Ib [37]. Therefore, we decided to compare the activity of LNA/DNA with that of BNA NC /DNA oligomers as EGSs.…”
Section: Resultsmentioning
confidence: 99%
“…Although LNA/DNAs show a degree of gymnotic uptake by some bacterial species, the levels of internalization seem not enough for effective EGS activity [62]. A strategy to increase the internalization efficiency is to conjugate them to CPPs [37, 63–66]. Chemical conjugation and purification of negatively charged oligonucleotide analogs with CPPs, which are usually cationic, has been quite difficult [67].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although considerable efforts are dedicated to designing new aminoglycosides that can overcome existing mechanisms of resistance [4, 9], other alternatives to counter the action of aminoglycoside modifying enzymes are being researched. They include the utilization of inhibitors of gene expression such as antisense oligonucleotide analogs [10-12], inhibitors of the enzymatic activity like those developed to overcome β-lactamase-mediated resistance to β-lactams [5, 13-18], or metal ion inhibitors of the acetylation reaction, which most probably act by protective chelation of the substrate antibiotic [19-22]. However, in spite of the efforts directed at designing inhibitors of aminoglycoside modifying enzymes or their expression, none are in use in the clinics yet [reviewed in 4, 5].…”
Section: Introductionmentioning
confidence: 99%